(untitled) (Jurnal Kemanusiaan, 2017)
ABSTRACT Questionnaires were used to investigate the effect of parenting practices on early adult students’ self-esteem. The findings show that the majority of the early adult students have the perception that a parent or primary guardian have a high level of involvement and modest in giving autonomy. While the level of rigor and supervision of parents also produces a moderate results. The study also showed that most students early adulthood have a moderate level of self esteem in which there are no significant differences between male and female students. ABSTRAK Soal selidik telah digunakan dalam mengkaji pengaruh amalan keibubapaan terhadap penghargaan kendiri pelajar awal dewasa. Dapatan kajian menunjukkan majoriti pelajar peringkat awal dewasa mempunyai persepsi bahawa ibu bapa ataupun penjaga utama have a high level of involvement and modest in giving autonomy. Manakala tahap ketegasan dan penyeliaan ibu bapa pula menghasilkan keputusan sederhana. Kajian juga menunjukkan kebanyakan pelajar peringkat awal dewasa mempunyai tahap penghargaan kendiri yang sederhana di mana tiada perbezaan signifikan antara pelajar lelaki dan perempuan.